JUE insight: Migration, transportation infrastructure, and the spatial transmission of COVID-19 in China - LI, Bingjing (Institutional Knowledge at Singapore Management University, 2022)
This paper evaluates the impacts of migration flows and transportation infrastructure on the spatial transmission of COVID-19 in China. Prefectures with larger bilateral migration flows and shorter travel distances with Hubei, the epicenter of the outbreak, experienced a wider spread of COVID-19. In addition, richer prefectures with higher incomes were better able to contain the virus at the early stages of community transmission. Using a spatial general equilibrium model, we show that around 28% of the infections outside Hubei province can be explained by the rapid development in transportation infrastructure and the liberalization of migration restrictions in the recent decade.